Examination of picture books in terms of illustration and colour harmony with regards to appropriateness for children - (:unkn) unknown (Sakarya University, 2017)
Picture books have a significant place in children’s development and education with their properties of being informative, entertaining and being preparative for life. In picture books, the illustration particulars and colour harmony is as important as the story told, language and editing because of the fact that they reinforce the emotion that is aimed to be expressed and enhance the visual perception. If the visual language that is used in picture books starts the visual perception of child in early ages and supports it, the educational attainments we desire for children will be easier to achieve. If the picture books are prepared and printed as a result of a professional study by keeping the needs and expectations of the child, a significant step towards raising a generation that likes reading will be taken. The purpose of this research is to examine the illustrations and pictures aimed at children, in children picture books in terms of appropriateness for development of visual perception and illustration and colour harmony. The sample set of the research is 54 children's picture books that are originally written in Turkish, or translated into Turkish. The books are limited to the “picture books” that are chosen by the preschool teachers working Kadıköy district printed between the years of 2009 and 2014. The chosen picture books are also limited to the ones that are for 5-6 ages. The research method used is descriptive survey model used for qualitative research. The descriptive survey model is preferred because it consists of the interpretation of the data by scanning and evaluation of it within generalizations. This research has been supported by Marmara University Research Project Committee under Project number EGT-D-120417-0231. © The Turkish Online Journal of Educational Technology.